Polymer composition for electrolyte and / or positive electrode of rechargeable battery
By using polymer compositions containing cationic monopole conductive polymers, plasticizers and ionic non-conductive fluoropolymers, the problem of low conductivity of lithium metal polymer batteries at room temperature is solved, and high lithium ion migration number is achieved Combination with good mechanical properties.
Patent Information
- Application Number
- CN202380053541.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-07-10
- Publication Date
- 2025-02-14
AI Technical Summary
The solid polymer electrolytes of existing lithium metal polymer batteries have low ionic conductivity at room temperature and require a higher operating temperature to improve conductivity, but the electrolyte loses dimensional stability at high temperatures and the addition of plasticizers will lead to machinery. Degradation of nature.
The ionic conductivity of the polymer composition is significantly improved by combining these components using polymer compositions containing cationic monopole conductive polymers, plasticizers, and ionic non-conductive fluoropolymers.
A polymer electrolyte suitable for lithium rechargeable batteries or sodium rechargeable batteries is achieved with high lithium ion migration numbers and improved ionic conductivity at lower temperatures while maintaining good mechanical strength.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] The present invention relates to the field of rechargeable batteries, more specifically to lithium rechargeable batteries or sodium rechargeable batteries, in particular for the production of electric vehicles and / or the storage of intermittent energy sources such as wind and / or solar energy.
[0002] The present invention more specifically relates to a polymer composition with improved ion conductive properties, the use of such a polymer composition for preparing a polymer electrolyte and / or a positive electrode for a rechargeable battery, a polymer electrolyte for a rechargeable battery comprising such a polymer composition, a positive electrode for a rechargeable battery comprising such a polymer composition, and a lithium rechargeable battery or a sodium rechargeable battery comprising such a polymer electrolyte and / or such a positive electrode.
[0003] The lithium metal polymer battery (or LMP) currently on the market ® ) is an "all-solid-state" battery, which is usually in the form of a thin film that is wound several times or several stacked thin films. This wound or stacked film has a thickness of about one hundred micrometers. It usually includes at least four functional membranes: a negative electrode (anode) that ensures the supply of lithium ions during discharge; a positive electrode (cathode) that acts as a container in which lithium ions are embedded; a solid polymer electrolyte that conducts lithium ions and is located between the positive and negative electrodes; and a current collector connected to the positive electrode to ensure electrical connection. The negative electrode usually consists of a lithium metal sheet or a lithium alloy sheet; the solid polymer electrolyte usually consists of a polymer based on poly(ethylene oxide) (PEO) and at least one lithium salt; the positive electrode contains an active electrode material, which is usually based on a metal oxide (such as V 2 O 5 ,LiV 3 O 8 、LiCoO 2 、LiNiO 2 、LiMn 2 O 4 or LiNi 0.5 Mn 0.5 O 2 ) or phosphate-based, such as LiMPO 4 , wherein M represents a metal cation selected from Fe, Mn, Co, Ni and Ti and combinations thereof, and optionally carbon; and the current collector is typically made of a metal sheet.
[0004] Solid polymer electrolytes offer great advantages in terms of safety, since they avoid the use of solvents that are potentially dangerous in the event of overheating. As a result, such batteries can operate at high temperatures without the risk of explosion. However, commonly used solid polymer electrolytes, such as high molecular weight PEO doped with lithium salts, have low ionic conductivity at room temperature, so their operating temperatures must be kept relatively high (typically 70°C to 100°C). But at these temperatures, PEO becomes a viscous liquid and loses its dimensional stability. In addition, attempts to improve the ionic conductivity of PEO by adding plasticizers have led to degradation of mechanical properties.
[0005] The ionic conductivity of an electrolyte characterizes the ability of charged ions to pass through the electrolyte. The higher it is, the greater the internal ion movement. If the ionic conductivity of a polymer electrolyte is at least 10 -5 S / cm, it can be considered to be of interest. The migration number of an ion is denoted t, which represents the fraction of the applied current that the ion will migrate in the electrolyte. t ranges from 0 to 1. Since lithium ions are the ions that participate in the chemical reactions that occur at the electrodes of lithium metal polymer batteries, it is desirable for the electrolyte to have a migration number t as close to 1 as possible. In solid polymer electrolytes, such as PEO doped with lithium salts, the charge fraction carried by lithium ions is low (approximately 0.2) due to the strong interaction between lithium cations and PEO chains, which limits the electrical performance. The low cation migration number leads to the formation of a salt concentration gradient in the thickness of the electrolyte during battery operation. This behavior produces salt loss at the electrodes, resulting in increased electrolyte resistance and reduced power performance, and favors the formation of lithium dendrites, resulting in reduced Faradaic efficiency and, ultimately, short circuits.
[0006] In order to obtain values of t close to 1, polymers have been described in which the anions form covalent bonds with the polymer chains and in which the counterions of the lithium are the only mobile species.
[0007] In particular, Meziane et al. (Electrochimica Acta, 2011, 57, 14-19) describe the preparation of polystyrene with sulfonyl (trifluoromethylsulfonyl) imide groups by free radical polymerization of sodium 4-phenylene-sulfonyl (trifluoromethylsulfonyl) imide monomers. This ionic polystyrene is then mixed with PEO to produce an electrolyte membrane that does not contain other lithium ions. However, the results obtained show that for temperatures below 60°C, the ionic conductivity is relatively low (e.g., about 3.1×10 -6 S / cm).
[0008] Therefore, the object of the present invention is to overcome the disadvantages of the aforementioned prior art and to provide a polymer composition which exhibits improved ionic conductive properties and a high lithium ion transference number while ensuring good mechanical strength so that it can be used as a polymer electrolyte for rechargeable batteries, in particular lithium rechargeable batteries or sodium rechargeable batteries.
[0009] The objects of the present invention are achieved by the following polymer composition.
[0010] In fact, the inventors of the present application have surprisingly discovered that it is possible to add an ionically non-conductive fluoropolymer to a specific cationic unipolar conducting polymer in association with a plasticizer in order to significantly improve the ionic conductivity of the polymer composition.
[0011] Polymer composition
[0012] Therefore, a first object of the present invention is a polymer composition characterized in that it comprises at least one cationic unipolar conducting polymer, which is a homopolymer or copolymer comprising at least one organic polymer chain, organic anionic functional groups forming covalent bonds with the organic polymer chain and metal cations associated with the organic anionic functional groups (ionic), at least one plasticizer and at least one ionically non-conductive fluoropolymer.
[0013] The combination of a cationic unipolar conducting polymer, a plasticizer and an ionically non-conductive fluoropolymer as defined above results in a polymer composition having improved ionically conducting properties.
[0014] Cationic monopolar conducting polymer
[0015] In the present invention, cationic unipolar conductive polymer refers to a polymer (homopolymer or copolymer) comprising at least one organic polymer chain, an organic anion functional group forming a covalent bond with the organic polymer chain, and a metal cation associated with the organic anion functional group. These metal cations are mobile species responsible for polymer ion conduction. In other words, the organic anion functional group is grafted onto the organic polymer chain and / or is a pendant to the organic anion functional group.
[0016] The term "organic polymer chain" refers to a polymer chain that is free of metals and metalloids. In other words, the organic polymer chain does not contain a metal or a metalloid such as silicon, or is different from a polysiloxane chain, or does not contain Si-O bonds.
[0017] The term "organic anionic functional group" refers to an anionic functional group that does not contain metals and semimetals. In other words, the organic anionic functional group does not contain metals or semimetals such as silicon, or does not contain Si-O bonds.
[0018] The cationic monopolar conductive polymer of the present invention is a polymer comprising an organic anion repeating unit (an organic polymer chain and an organic anion functional group covalently bonded to the organic chain) which is associated with a metal cation (ionic).
[0019] The cationic monopolar conducting polymer is preferably obtained by free-radical polymerization, in particular using at least one monomer comprising at least one organic anionic functional group covalently grafted onto said monomer and at least one metal cation associated with the organic anionic functional group.
[0020] Cationic monopolar conducting polymers can be:
[0021] - a homopolymer obtainable from a) a monomer comprising at least one organic anionic functional group covalently grafted onto said monomer and at least one metal cation associated with the organic anionic functional group; or
[0022] - copolymers, which can be prepared from a) monomers comprising at least one organic anionic functional group covalently grafted onto said monomer and at least one metal cation associated with the organic anionic functional group, and b) at least one other monomer different from monomer a), said other monomer being selected from b1) monomers comprising at least one organic anionic functional group covalently grafted onto said monomer and at least one metal cation associated with the organic anionic functional group, and b2) organic monomers.
[0023] The term "organic monomer b2)" refers to monomers which are free of metals and semimetals. In other words, the organic monomer does not contain a metal or a semimetal such as silicon, and / or is not a compound containing Si-O bonds.
[0024] The (monomeric) metal cation or (polymeric) metal cation associated with the organic anionic functional group is preferably selected from Li + Cations and Na + cation, and particularly preferably Li + cation.
[0025] Monomer a) or monomer b1), i.e., a monomer comprising at least one organic anion functional group covalently grafted onto the monomer and at least one metal cation associated with the organic anion functional group, may be selected from aromatic vinyl monomers and non-aromatic vinyl monomers, wherein the monomer comprises at least one organic anion functional group covalently grafted onto the organic monomer and at least one metal cation associated with the organic anion functional group.
[0026] Examples of the aromatic vinyl monomer include styrene and its derivatives.
[0027] The styrene derivative is preferably a derivative in which the phenyl moiety of styrene is substituted with one or more than one group selected from the group consisting of a methyl group, an ethyl group and a tert-butyl group.
[0028] Examples of non-aromatic vinyl monomers include acrylates, methacrylates, acrylamides, methacrylamides, ethylene, propylene, dienes or maleimides.
[0029] The organic monomer b2) may be vinylidene fluoride, a phosphate, a phosphonate, an ether, a carbonate, a malonate, an amide, an acrylate, an anhydride or an ester.
[0030] In this embodiment, the copolymer comprises vinylidene fluoride repeating units, phosphate repeating units, phosphonate repeating units, ether repeating units, carbonate repeating units, malonate repeating units, amide repeating units, acrylate repeating units, anhydride repeating units, or ester repeating units in addition to the organic anion repeating units associated with the metal cation.
[0031] The organic anion functional group (of monomer a) and monomer b1)) or the organic anion functional group (of the polymer) may be selected from sulfonate functional groups, borate functional groups and imidide functional groups.
[0032] The organic anionic functional group is preferably an imide, particularly preferably a bissulfonylimide, more particularly preferably sulfonyl(trifluoromethanesulfonyl)imide (TFSI) or sulfonyl(fluorosulfonyl)imide (FSI), and even more particularly preferably sulfonyl(trifluoromethanesulfonyl)imide (TFSI).
[0033] According to a particularly preferred embodiment of the present invention, the monomer comprises at least one organic anion imide functional group covalently grafted to the monomer and Li as the metal cation associated with the organic anion imide functional group. + The aromatic vinyl monomer or non-aromatic vinyl monomer is selected from the following monomers (Ia) to (Ii):
[0034] .
[0035] The cationic monopolar conductive polymer is preferably polystyrene-sulfonyl (trifluoromethylsulfonyl) imide lithium (PSTFSILi) or polymethacrylate-sulfonyl (trifluoromethylsulfonyl) imide lithium (PMTFSILi).
[0036] The number average molar mass (ie, Mn) of the cationic monopolar conductive polymer is preferably about 10,000 to 1,000,000 g / mol, and particularly preferably about 50,000 to 700,000 g / mol.
[0037] In the present invention, the number average molecular weight is measured by a method well known to those skilled in the art, and in particular by gel permeation chromatography (GPC).
[0038] The cationic monopolar conductive polymer is preferably about 5% to 40% by mass, even more particularly preferably about 5% to 30% by mass, relative to the total mass of the polymer composition.
[0039] The cationic unipolar conducting polymer already comprises anionic functional groups (anionic groups derived from lithium or sodium salts directly grafted into the polymer material structure). Therefore, the polymer composition preferably does not comprise other or supplementary one or more than one lithium or sodium salt, such as molecular lithium or molecular sodium salts (i.e. lithium or sodium salts not grafted into the polymer material).
[0040] Ion-non-conductive fluoropolymers
[0041] In the present invention, the ion-nonconductive polymer is a polymer that does not allow the conduction of lithium ions or sodium ions. In other words, the ion conductivity of the ion-nonconductive polymer is less than 10 -7 S / cm, especially at operating temperature.
[0042] The ion-nonconductive fluorinated polymer is preferably about 5 to 45% by mass, even more particularly preferably about 5 to 40% by mass, relative to the total mass of the polymer composition.
[0043] The ion-nonconducting polymer is fluorinated. In other words, it is a polymer whose repeating unit is a fluorocarbon and therefore contains multiple carbon-fluorine bonds.
[0044] The ion-nonconductive fluorinated polymer of the polymer composition of the present invention can be selected from homopolymers and copolymers of vinyl fluoride (VF), homopolymers and copolymers of vinylidene fluoride (VdF), homopolymers and copolymers of tetrafluoroethylene (TFE), homopolymers and copolymers of chlorotrifluoroethylene (CTFE), homopolymers and copolymers of hexafluoropropylene (HFP), and mixtures thereof.
[0045] According to a particularly preferred embodiment of the invention, the ion-nonconductive fluoropolymer is selected from homopolymers and copolymers of vinylidene fluoride (VdF), such as PVdF or P(VdF-HFP).
[0046] According to a more particularly preferred embodiment, the ionically non-conductive fluoropolymer is PVdF.
[0047] The weight ratio of the non-conductive fluorine-containing polymer to the cationic monopolar conductive polymer in the polymer composition is preferably about 20 / 80 to 90 / 10, and particularly preferably about 40 / 60 to 80 / 20.
[0048] The ion-nonconductive fluoropolymer preferably has a number average molar mass (ie, Mn) of about 50,000 to 1,300,000 g / mol.
[0049] Plasticizers
[0050] The polymer composition comprises at least one plasticizer.
[0051] Plasticizers are non-aqueous solvents that are able to form a gel-like polymer composition.
[0052] The non-aqueous solvent or plasticizer may be selected from:
[0053] - linear and cyclic carbonates, for example propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) or methyl isopropyl carbonate (MiPC);
[0054] - fluorinated carbonates, for example fluoroethylene carbonate;
[0055] - nitriles, for example succinonitrile;
[0056] - lactones, for example γ-butyrolactone;
[0057] - liquid linear polyethers and liquid cyclic polyethers, for example dimethyl ether, polyethylene glycol dimethyl ether (or PEGDME), for example tetraethylene glycol dimethyl ether (TEGDME), or dioxolanes;
[0058] - fluorinated polyethers;
[0059] - sulfur solvents, such as sulfolane or dimethyl sulfoxide;
[0060] - phosphates, for example triethyl phosphate or fluorophosphate;
[0061] - esters, such as ethyl acetate or ethyl butyrate (EB); and
[0062] - mixtures thereof.
[0063] Among these solvents or plasticizers, linear carbonates and cyclic carbonates are particularly preferred.
[0064] The solvent or plasticizer is preferably about 25 to 90 wt %, particularly preferably about 35 to 90 wt %, and even more preferably about 65 to 90 wt %, based on the total weight of the polymer composition.
[0065] Additives in polymer compositions
[0066] The polymer composition of the invention may also comprise reinforcing agents. This thus enables the mechanical properties of the polymer composition to be adjusted.
[0067] The reinforcing agent is preferably selected from cellulose nanofibers and ceramic nanoparticles, such as titanium oxide nanoparticles, aluminum oxide nanoparticles or silicon oxide nanoparticles.
[0068] According to a particularly preferred embodiment of the present invention, the polymer composition comprises (or consists of):
[0069] - about 40% to 90% by weight of plasticizer, and preferably about 65% to 90% by weight of plasticizer,
[0070] - about 5% to 35% by weight of an ionically non-conductive fluoropolymer, and
[0071] - about 5% to 35% by weight of a cationic monopolar conducting polymer.
[0072] In fact, the mixture of the ion-nonconductive fluoropolymer and the cationic unipolar conductive polymer is able to absorb the plasticizer while maintaining good mechanical strength and remaining solid or quasi-solid. In addition, the presence of the plasticizer results in a solid polymer composition or a quasi-solid polymer composition having improved ionic conductivity (e.g., at least 1×10 -5 S / cm).
[0073] The polymer composition of the present invention is preferably prepared by mixing the various components, namely the cationic unipolar conductive polymer, the plasticizer and the ion-nonconductive fluoropolymer. In particular, the components (ion-nonconductive fluoropolymer, cationic unipolar conductive polymer and plasticizer) are mixed in an organic solvent such as acetonitrile, advantageously under magnetic stirring. The mixing can be carried out under heating, in particular at a temperature of at least 50°C, preferably at least 80°C, even more preferably at least 90°C. The resulting mixture can then be deposited on a substrate by coating, advantageously at room temperature (e.g. 18°C to 25°C). Drying can then be carried out, in particular to remove the organic solvent.
[0074] Use of polymer compositions
[0075] The second object of the present invention is the use of the polymer composition defined in the first object of the present invention for preparing a polymer electrolyte and / or a positive electrode for a rechargeable battery, wherein the rechargeable battery is preferably a lithium rechargeable battery or a sodium rechargeable battery, particularly preferably a lithium metal battery or a sodium metal battery, and more particularly preferably a lithium metal battery.
[0076] The use of the polymer composition according to the invention for preparing a polymer electrolyte for a rechargeable lithium battery results in an energy storage device having excellent low temperature properties (i.e. <60°C, and preferably ≤40°C), in particular a lithium ion transference number of about 1 at a temperature of up to 40°C and an ionic conductivity greater than or equal to 10 -5 S cm-1 , preferably greater than or equal to 5×10 -5 S cm -1 , and particularly preferably greater than or equal to 10 -4 S cm -1 . A high migration number limits the formation of concentration gradients in the polymer electrolyte during discharge (respectively charging), thereby improving the power performance (respectively charging speed). The use of such a polymer composition also makes it possible to limit the dendrite growth of lithium and thus envisage a fast and safe recharging. This is because a problem with lithium metal battery technology is the formation of heterogeneous lithium electrodeposits (including dendrites) during recharging, which reduces the cyclability and may lead to short circuits. The polymer compositions according to the invention also exhibit good mechanical strength, high thermal stability (which ensures the safety of energy storage devices containing them) and improved potential stability (for example, relative to Li + / Li up to 4.5V stability).
[0077] The use of the polymer composition according to the present invention for preparing the positive electrode of a rechargeable lithium metal battery or a rechargeable sodium metal battery can improve the ionic conductivity, thereby reducing the operating temperature of the battery and improving its power response. The polymer composition also improves the adhesion of the positive electrode to the current collector.
[0078] Polymer Electrolyte
[0079] A third object of the present invention is a polymer electrolyte for rechargeable batteries, characterized in that it comprises the polymer composition according to the first object of the present invention, or a porous separator impregnated with the polymer composition according to the first object of the present invention.
[0080] The porous separator may be made of an electronically non-conductive porous material, preferably a porous polymer material based on at least one polyolefin, such as polyethylene or polypropylene, or fibers, such as glass fibers or wood fibers.
[0081] The polymer electrolyte is preferably in the form of a thin film, particularly preferably in the form of a thin film having a thickness of about 5 μm to 45 μm, more preferably about 10 μm to 25 μm.
[0082] When the polymer electrolyte comprises (or consists of) a porous separator impregnated with the polymer composition according to the first object, the porous separator is preferably coated with the polymer composition on a first side and on a second side facing the first side.
[0083] Polymer (solid or quasi-solid) electrolytes may be prepared by any technique well known to those skilled in the art, for example by coating, extrusion or pressing (cold or hot).
[0084] The polymer electrolyte is preferably applicable to a rechargeable lithium battery or a rechargeable sodium battery, particularly preferably applicable to a lithium metal battery or a sodium metal battery, and even more preferably applicable to a lithium metal battery.
[0085] positive electrode
[0086] A fourth object of the present invention is a positive electrode for a rechargeable battery, comprising a positive electrode active material, a polymer composition and optionally an electron conductivity generator, characterized in that the polymer composition is as defined in the first object of the present invention.
[0087] The positive electrode is preferably applicable to a rechargeable lithium battery or a rechargeable sodium battery, particularly preferably applicable to a lithium metal battery or a sodium metal battery, and even more preferably applicable to a lithium metal battery.
[0088] Positive electrode active material
[0089] The active material of the positive electrode is a reversible active material of lithium ions or sodium ions. In other words, lithium ions or sodium ions can be reversibly intercalated or deintercalated.
[0090] The positive electrode active material can be:
[0091] -Metal oxides, such as vanadium oxide VO x (2≤x≤2.5), LiV 3 O 8 , Li y Ni 1-x Co x O 2 (0≤x≤1; 0≤y≤1), manganese spinel Li y Mn 1-x M x O 2 (M=Cr, Al, V, Ni, 0≤x≤0.5; 0≤y≤2), V 2 O 5 , lithium oxides such as LiCoO 2 、LiNiO 2 、LiMn 2 O 4 、LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 (NMC), LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA) and LiNi 0.5 Mn 0.5 O 2 ,
[0092] -phosphosilicates or metal phosphates, such as Li3 V 2 (PO 4 ) 3 or LiMPO 4 , wherein M represents a metal cation selected from Fe, Mn, Co, Ni, Ti, and combinations thereof, or
[0093] -Metal sulfates, such as iron sulfate Fe 2 (SO 4 ) 3 .
[0094] The active material of the positive electrode may be about 50% to 90% by mass, preferably about 55% to 80% by mass, relative to the total mass of the positive electrode.
[0095] Electron conductivity generator
[0096] The electron conductivity generating agent may be selected from carbon black, acetylene black, carbon fibers and nanofibers, carbon nanotubes, graphene, graphite, metal particles and metal fibers of at least one conductive metal such as aluminum, platinum, iron, cobalt and nickel, and mixtures thereof.
[0097] The electron conductivity generating agent is preferably carbon black.
[0098] The electron conductivity generating agent may be about 0.1% to 10% by mass, and preferably about 0.5% to 5% by mass, relative to the total mass of the positive electrode.
[0099] Polymer composition
[0100] The polymer composition is the polymer composition defined in the first object of the present invention.
[0101] The polymer composition may be about 10% to 49.5% by mass, preferably about 20% to 40% by mass, relative to the total mass of the positive electrode.
[0102] The positive electrode preferably does not contain a lithium molecular salt or a sodium molecular salt.
[0103] The positive electrode is preferably in the form of a thin film, which typically has a thickness of about 20 microns to 100 microns.
[0104] Rechargeable lithium battery or rechargeable sodium battery
[0105] A fifth object of the present invention is a rechargeable lithium battery or a rechargeable sodium battery, characterized in that it comprises:
[0106] - a negative electrode comprising lithium metal, sodium metal, a lithium metal alloy or a sodium metal alloy,
[0107] - a positive electrode, which may be supported by a current collector, and
[0108] - a polymer electrolyte, which is located between the positive and negative electrodes,
[0109] The invention is characterized in that the polymer electrolyte is as defined in the third object of the invention, and / or the positive electrode is as defined in the fourth object of the invention.
[0110] negative electrode
[0111] The negative electrode is preferably in the form of a thin film, the thickness of which is generally about 1 micrometer to 100 micrometers.
[0112] The negative electrode may be composed of lithium metal, sodium metal, one of lithium alloys such as alloys of lithium with sodium, silicon, tin, aluminum, magnesium, silver, zinc or germanium, or one of sodium alloys such as alloys of sodium with lithium, silicon, tin, magnesium, silver, zinc or germanium, silver, zinc or germanium.
[0113] The negative electrode preferably consists of lithium metal or one of its alloys.
[0114] positive electrode
[0115] The positive electrode may be the positive electrode according to the fourth aspect of the present invention, or the positive electrode may include a positive electrode active material, a polymer binder, an optional plasticizer, and an optional electron conductivity generator.
[0116] The positive electrode active material and the electron conductivity generating agent are as defined in the fourth object of the present invention.
[0117] Plasticizers
[0118] The plasticizer (or non-aqueous solvent) may be selected from:
[0119] - linear and cyclic carbonates, for example propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) or methyl isopropyl carbonate (MiPC);
[0120] - fluorinated carbonates, for example fluoroethylene carbonate;
[0121] - nitriles, such as succinonitrile;
[0122] - lactones, for example γ-butyrolactone;
[0123] - liquid linear or liquid cyclic polyethers, for example dimethyl ether, polyethylene glycol dimethyl ether (or PEGDME), for example tetraethylene glycol dimethyl ether (TEGDME), or dioxolane;
[0124] - fluorinated polyethers;
[0125] - Sulfur solvents, such as sulfolane or dimethyl sulfoxide;
[0126] - phosphates, for example triethyl phosphate or fluorophosphate;
[0127] - esters, such as ethyl acetate or ethyl butyrate (EB); and
[0128] - mixtures thereof.
[0129] Among these solvents or plasticizers, linear carbonates and cyclic carbonates are particularly preferred.
[0130] The plasticizer of the positive electrode may be about 5% to 35% by mass, preferably about 10% to 25% by mass, relative to the total mass of the positive electrode.
[0131] Polymer Binder
[0132] The polymer binder may be selected from homopolymers and copolymers of ethylene, homopolymers and copolymers of propylene; homopolymers and copolymers of ethylene oxide (e.g., PEO, copolymers of PEO), formaldehyde, propylene oxide, epichlorohydrin, allyl glycidyl ether, and mixtures thereof; halogenated polymers, such as homopolymers and copolymers of vinyl chloride, vinylidene fluoride (PVdF), vinylidene chloride, tetrafluoroethylene or trifluorochloroethylene, or mixtures thereof; electronically non-conductive anionic polymers, such as poly(styrene sulfonate), poly(acrylic acid), poly(glutamate), alginate, pectin, gelatin or mixtures thereof; cationic polymers, such as polyethyleneimine (PEI), emeraldine salt, ES) form of polyaniline, quaternized poly(N-vinylimidazole), poly(acrylamide-diallyldimethylammonium chloride) (AMAC) or mixtures thereof; polyacrylates; elastomers, such as homopolymers or copolymers of ethylene, propylene, styrene, butadiene or chloroprene; cationic unipolar conductive polymers; and mixtures thereof.
[0133] The cationic monopolar conducting polymer may be as defined in the first aspect of the present invention.
[0134] The polymer binder may be included in an amount of about 5% to 35% by mass, preferably about 10% to 25% by mass, relative to the total mass of the positive electrode.
[0135] According to a preferred embodiment of the invention, the active material of the positive electrode is coated with a carbon layer. The presence of the carbon layer enables to improve the interface: active material - polymer binder.
[0136] The carbon coating the active material is preferably about 0.1% to 5% by mass relative to the mass of the active material.
[0137] The carbon layer is preferably in the form of a layer having a thickness of approximately 1 nm to 4 nm.
[0138] The positive electrode may also contain a lithium salt or a sodium salt, particularly when the polymer binder is not a cationic monopolar conducting polymer.
[0139] According to a particularly preferred embodiment of the present invention, the positive electrode is a positive electrode that meets the fourth object of the present invention.
[0140] current collector
[0141] The rechargeable battery may further include a current collector connected to the positive electrode.
[0142] The current collector usually consists of a metal sheet.
[0143] The current collector is preferably a current collector made of stainless steel or aluminum, optionally covered with a carbon-based layer (anti-corrosion layer).
[0144] Polymer Electrolyte
[0145] The polymer electrolyte may be a polymer electrolyte that meets the third object of the present invention, or the polymer electrolyte may comprise a cationic monopolar conductive polymer; or a combination of at least one lithium salt and at least one polymer material selected from a polymer material based on polyethylene oxide (PEO), a polycarbonate and a polydiester.
[0146] The poly(ethylene oxide) (PEO)-based polymer material can be selected from polystyrene-poly(ethylene oxide) (PS-b-PEO) block copolymers, polystyrene-poly(ethylene oxide)-polystyrene (PS-b-PEO-b-PS) block copolymers, random poly(ethylene oxide-co-propylene oxide) copolymers (i.e., PEO-ran-PPO), random poly(ethylene oxide-co-butylene oxide) copolymers (i.e., PEO-ran-PBO), poly(ethylene oxide), and mixtures thereof.
[0147] The lithium salt used in combination with the poly(ethylene oxide)-based polymer material may be selected from lithium fluoride (LiFO 3 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF 6 ), lithium fluoroborate (LiBF 4 ), lithium metaborate (LiBO 2 ), lithium perchlorate (LiClO 4 ), lithium nitrate (LiNO 3 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(pentafluoroethyl)imide (LiBETI), LiAsF 6 、LiCF 3 SO 3 、LiSbF 6 、LiSbCl 6 , Li 2 TiCl 6 , Li 2 SeCl 6 , Li 2B 10 Cl 10 , Li 2 B 12 Cl 12 , lithium bis(oxalato)borate (LiBOB), and mixtures thereof.
[0148] The lithium salt is preferably 5% by mass to 30% by mass, and even more preferably 10% by mass to 25% by mass, relative to the total mass of the polymer electrolyte.
[0149] The poly(ethylene oxide) (PEO) based polymer material may be combined with a reinforcing agent. This can thus adjust the mechanical properties of the polymer material.
[0150] The reinforcing agent is preferably selected from cellulose nanofibers, ceramic nanoparticles such as titanium oxide, aluminum oxide or silicon oxide nanoparticles, and fluorinated polymers and fluorinated copolymers such as polyvinylidene fluoride (PVdF) or copolymers of vinylidene fluoride-hexafluoropropylene (PVdF-co-HFP).
[0151] The cationic monopolar conducting polymer may be as defined in the first aspect of the present invention.
[0152] According to a particularly preferred embodiment of the present invention, the polymer electrolyte is a polymer electrolyte that meets the third object of the present invention.
[0153] The present invention is illustrated by the following embodiments, but the present invention is not limited to these embodiments.
[0154] The accompanying drawings illustrate the invention.
[0155] Figure 1 The S·cm of the conventional polymer electrolyte and the polymer electrolyte of the present invention are shown. -1 The ionic conductivity of -1 ) function changes.
[0156] Figure 2 The S·cm of the conventional polymer electrolyte and the polymer electrolyte of the present invention are shown. -1 The ionic conductivity of -1 ) function changes.
[0157] Figure 3 The S·cm of the conventional polymer electrolyte and the polymer electrolyte of the present invention are shown. -1 The ionic conductivity of -1 ) function changes.
[0158] Figure 4 The S·cm of conventional polymer electrolytes is shown. -1The ionic conductivity of -1 ) function changes.
[0159] Figure 5 The inverse of the imaginary part of the impedance in Ω -Z" of a conventional positive electrode and a positive electrode of the present invention is shown as a function of the real part of the impedance in Ω Z'.
[0160] Figure 6 The capacity (in mAh / g) and the efficiency (in %) of a battery according to the invention are shown as a function of the number of cycles.
[0161] Figure 7 The internal resistance Ri (in Ω·cm) of the battery according to the present invention is shown. 2 ) as a function of the number of discharge cycles and the number of charge cycles.
[0162] Figure 8 The capacity (in mAh / g) and the efficiency (in %) of a battery according to the invention are shown as a function of the number of cycles.
[0163] Fig. 9 The internal resistance Ri (in Ω·cm) of the battery according to the present invention is shown. 2 ) as a function of the number of discharge cycles and the number of charge cycles.
[0164] Fig.10 The S·cm of the conventional polymer electrolyte and the polymer electrolyte of the present invention are shown. -1 The ionic conductivity of -1 ) function changes. Example
[0165] The raw materials used in the examples are listed below:
[0166] -Carbon black, Sumitomo Corp, reference "ECP-600JD",
[0167] - Lithium manganese iron phosphate (LMFP), Huayi, level 2,
[0168] - PVDF, sold by Solvay as "5130", molar mass Mw = 900000 g / mol,
[0169] - PVdF-HFP, sold by Arkema as "Kynarflex 2751",
[0170] -Propylene carbonate (PC), Aldrich, anhydrous, purity 99.7%,
[0171] -Triethyl phosphate (TEP), TCI, purity> 99.0%,
[0172] -PMTFSI: Poly((trifluoromethane)sulfonyl imide lithium methacrylate), Specific Polymers, molar mass Mn = 238330 g / mol,
[0173] -PSTFSI: poly(styrene tri(fluoromethane)sulfonimide), molar mass Mn=84720 g / mol,
[0174] -PMMA: poly(methyl methacrylate), Sigma-Aldrich, Mw about 996000 g / mol,
[0175] -Acetonitrile, Sigma-Aldrich, anhydrous, purity 99.8%,
[0176] -Lithium metal foil, Ganfeng extruded and laminated to 72µm,
[0177] -Lithium metal electrode, Ganfeng extruded and laminated to 72µm,
[0178] -72μm thick lithium metal anode, Ganfeng extruded and then laminated to 72µm,
[0179] - "EnSafe 65" current collector, Armor.
[0180] Unless otherwise stated, all materials used were as obtained from the manufacturers.
[0181] Example 1: Preparation of polymer electrolyte EP1* not in accordance with the present invention and polymer electrolytes EP2, EP3, EP4 and EP5 in accordance with the present invention
[0182] As described in detail below, various polymer electrolytes were prepared that included PVdF as an ionically non-conductive fluoropolymer, PMTFSI as a cationically unipolar conducting polymer, and propylene carbonate as a plasticizer.
[0183] The components (ion-nonconductive fluoropolymer, cationic unipolar conductive polymer and plasticizer) were mixed with acetonitrile (ACN) in a beaker under magnetic stirring (300 rpm) at 100° C. For 1 g of the mixture of ion-nonconductive fluoropolymer and cationic unipolar conductive polymer, 1 g of plasticizer and 5 g of acetonitrile were used. After mixing, the resulting mixture was coated onto a silicone-coated polyethylene terephthalate (PET) support at 8 mm / s at room temperature to form a thin film, which was then dried in a fume hood for a few minutes to evaporate the residual acetonitrile.
[0184] Table 1 below shows the mass percentages of various components present in the electrolyte prepared according to the above scheme, as well as its thickness:
[0185]
[0186] Table 1
[0187] For each polymer electrolyte, a lithium electrolyte lithium (LEL) cell was then fabricated by sequentially laminating a lithium foil, the polymer electrolyte membrane prepared as above, and another lithium foil at 75° C. under dry air.
[0188] For the polymer electrolyte EP1* not in accordance with the invention, lamination was carried out at a pressure of 2 bar. For the other polymer electrolytes, EP2 to EP5, lamination was carried out at a pressure of 5 bar.
[0189] The cells LEL1*, LEL2, LEL3, LEL4 and LEL5, comprising polymer electrolytes EP1*, EP2, EP3, EP4 and EP5 respectively, are placed in a compression system at 2 bar.
[0190] The ionic conductivity of the polymer electrolytes EP1*, EP2, EP3, EP4 and EP5 was measured by impedance spectroscopy using a device sold under the trade name IM6EX by the Zahner company. The measurements were carried out at 20°C and 40°C in the potentiostatic mode from 100 mHz to 1 MHz and an amplitude of 10 mV using cells LEL1*, LEL2, LEL3, LEL4 and LEL5 prepared as above.
[0191] Figure 1 The S.cm of polymer electrolytes EP1* (curves with solid circles connected by solid lines), EP2 (curves with solid circles connected by wide dashed lines), EP3 (curves with solid circles connected by standard dashed lines), EP4 (curves with solid circles connected by short dashed lines) and EP5 (curves with solid triangles connected by solid lines) are shown. -1 The ionic conductivity is measured as a function of temperature (measured as 1000 / temperature, in Kelvin -1 The higher the PVdF content of the polymer electrolyte, the greater its ionic conductivity. The introduction of PVdF as an ion-nonconductive fluoropolymer helps to increase the ionic conductivity of the polymer electrolyte, which is based on at least one cationic unipolar conductive polymer such as PMTFSI and plasticized with at least one plasticizer such as propylene carbonate.
[0192] Example 2: Preparation of polymer electrolyte EP6* not in accordance with the present invention and polymer electrolytes EP7, EP8, EP9 and EP10 in accordance with the present invention
[0193] As described in detail below, various polymer electrolytes were prepared that included PVdF as an ionically non-conductive fluoropolymer, PSTFSI as a cationically unipolar conducting polymer, and propylene carbonate as a plasticizer.
[0194] The components (ion-nonconductive fluoropolymer, cationic unipolar conductive polymer and plasticizer) were mixed with acetonitrile (ACN) in a beaker under magnetic stirring (300 rpm) at 100° C. For 1 g of the mixture of ion-nonconductive fluoropolymer and cationic unipolar conductive polymer, 1 g of plasticizer and 5 g of acetonitrile were used. After mixing, the resulting mixture was coated onto a silicone-coated polyethylene terephthalate (PET) support at 8 mm / s at room temperature to form a thin film, which was then dried in a fume hood for a few minutes to evaporate the residual acetonitrile.
[0195] Table 2 below shows the mass percentages of the various components present in the electrolyte prepared according to the above scheme, as well as their thicknesses:
[0196]
[0197] Table 2
[0198] For each polymer electrolyte, a lithium electrolyte lithium (LEL) cell was then prepared by sequentially laminating a lithium foil, the polymer electrolyte membrane prepared as above, and another lithium foil at 75° C. under dry air.
[0199] For the polymer electrolyte not in accordance with the invention EP6*, lamination was performed at a pressure of 2 bar. In addition, two layers of polymer electrolyte EP6* were used to prevent short circuits. For the other polymer electrolytes in accordance with the invention, EP7 to EP10, lamination was performed at a pressure of 5 bar.
[0200] Cells LEL6*, LEL7, LEL8, LEL9 and LEL10 comprising polymer electrolytes EP6*, EP7, EP8, EP9 and EP10, respectively, were placed in a compression system at 2 bar.
[0201] The ionic conductivity of polymer electrolytes EP6*, EP7, EP8, EP9 and EP10 was measured as described in Example 1.
[0202] Figure 2 The S.cm of polymer electrolytes EP6* (curves with solid circles connected by solid lines), EP7 (curves with solid circles connected by wide dashed lines), EP8 (curves with solid circles connected by standard dashed lines), EP9 (curves with solid circles connected by short dashed lines) and EP10 (curves with solid triangles connected by solid lines) are shown. -1 The ionic conductivity is measured as a function of temperature (measured as 1000 / temperature, in Kelvin -1The introduction of PVdF as an ion-nonconductive fluoropolymer helps to increase the ionic conductivity of a polymer electrolyte based on at least one cationic unipolar conductive polymer such as PSTFSI and plasticized with at least one plasticizer such as propylene carbonate. The ionic conductivity reaches a maximum value when the PVdF content is 35% by mass relative to the total mass of the polymer electrolyte.
[0203] Example 3: Preparation of polymer electrolyte EP11* not in accordance with the present invention and polymer electrolytes EP12 and EP13 in accordance with the present invention
[0204] As described in detail below, various polymer electrolytes were prepared that included PVdF as an ionically non-conductive fluoropolymer, PMTFSI as a cationically unipolar conducting polymer, and triethyl phosphate (TEP) as a plasticizer.
[0205] The components (ion-nonconductive fluoropolymer, cationic unipolar conductive polymer and plasticizer) were mixed with acetonitrile (ACN) in a beaker under magnetic stirring (300 rpm) at 100° C. For 1 g of the mixture of ion-nonconductive fluoropolymer and cationic unipolar conductive polymer, 1 g of plasticizer and 5 g of acetonitrile were used. After mixing, the resulting mixture was coated onto a silicone-coated polyethylene terephthalate (PET) support at 8 mm / s at room temperature to form a thin film, which was then dried in a fume hood for a few minutes to evaporate the residual acetonitrile.
[0206] Table 3 below shows the mass percentages of various components present in the electrolyte prepared according to the above scheme, as well as its thickness:
[0207]
[0208] Table 3
[0209] For each polymer electrolyte, a lithium electrolyte lithium (LEL) cell was then prepared by sequentially laminating a lithium foil, the polymer electrolyte membrane prepared as above, and another lithium foil at 75° C. under dry air.
[0210] For the polymer electrolyte not in accordance with the invention EP11*, lamination was performed at a pressure of 2 bar and lithium electrodes were used instead of two lithium foils. For the other polymer electrolytes in accordance with the invention, EP12 to EP13, lamination was performed at a pressure of 5 bar.
[0211] The cells LEL11*, LEL12 and LEL13, comprising polymer electrolytes EP11*, EP12 and EP13 respectively, are placed in a compression system at 2 bar.
[0212] The ionic conductivity of polymer electrolytes EP11*, EP12 and EP13 was measured as described in Example 1.
[0213] Figure 3 The S·cm of polymer electrolytes EP11* (curve with solid circles connected by a solid line), EP12 (curve with solid squares), and EP13 (curve with solid circles connected by a dotted line) are shown. -1 The ionic conductivity is measured as a function of temperature (measured as 1000 / temperature, in Kelvin -1 The higher the PVdF content of the polymer electrolyte, the greater its ionic conductivity. The introduction of PVdF as an ion-nonconductive polymer helps to increase the ionic conductivity of the polymer electrolyte, which is based on at least one cationic unipolar conductive polymer such as PMTFSI and plasticized with at least one plasticizer such as triethyl phosphate.
[0214] Comparative Example 4: Preparation of polymer electrolytes EP14*, EP15* and EP16* not in accordance with the present invention
[0215] As described in detail below, various polymer electrolytes were prepared that included PMMA instead of PVdF as the ionically non-conductive non-fluorinated polymer, PMTFSI as the cationically unipolar conducting polymer, and propylene carbonate as the plasticizer.
[0216] The components (ion-non-conductive non-fluorinated polymer, cationic monopolar conductive polymer and plasticizer) were mixed with acetonitrile (ACN) in a beaker under magnetic stirring (300 rpm) at 100° C. For a mixture of 1 g of ion-non-conductive non-fluorinated polymer PMMA and cationic monopolar conductive polymer, 1 g of plasticizer and 5 g of acetonitrile were used. After mixing, the resulting mixture was coated onto a silicone-coated polyethylene terephthalate (PET) support at room temperature at 8 mm / s to form a thin film, which was then dried in a fume hood for a few minutes to evaporate the residual acetonitrile.
[0217] Table 4 below shows the mass percentages of various components present in the electrolyte prepared according to the above scheme, as well as its thickness:
[0218]
[0219] Table 4
[0220] For each polymer electrolyte, a lithium electrolyte lithium (LEL) cell was then prepared by sequentially laminating a lithium foil, the polymer electrolyte membrane prepared as above, and another lithium foil at 75° C. under dry air.
[0221] For the polymer electrolyte EP1* not in accordance with the invention, lamination was carried out at a pressure of 2 bar. For the other polymer electrolytes not in accordance with the invention, EP14* to EP16*, lamination was carried out at a pressure of 5 bar.
[0222] Cells LEL1*, LEL14*, LEL15* and LEL16* comprising polymer electrolytes EP1*, EP14*, EP15* and EP16*, respectively, were placed in a 2 bar compression system.
[0223] The ionic conductivity of the polymer electrolytes EP1*, EP14*, EP15* and EP16* was measured as in Example 1.
[0224] Figure 4 The S·cm of polymer electrolytes EP1* (curve with solid circles connected by solid lines), EP14* (curve with solid circles connected by wide dashed lines), EP15* (curve with solid circles connected by standard dashed lines), and EP16* (curve with solid circles connected by short dashed lines) are shown. -1 The ionic conductivity is measured as a function of temperature (measured as 1000 / temperature, in Kelvin -1 Unlike PVdF, the use of PMMA reduces the ionic conductivity of the polymer electrolyte.
[0225] Example 5: Preparation of cathodes C1* not in accordance with the invention and cathodes C2 in accordance with the invention
[0226] Preparation of cathodes C1* and C2
[0227] The first cathode (positive electrode) C1* in the form of a thin film not in accordance with the present invention (i.e., without PVdF as an ion-nonconductive fluoropolymer) was prepared as follows: 1.32 g of propylene carbonate (PC), 1.32 g of PMTFSI and 12 g of ACN were mixed in a beaker at 100° C. and 300 rpm under magnetic stirring. Then, when a uniform result was obtained, 4.2 g of lithium manganese iron phosphate (LMFP) and 0.17 g of carbon black (KB) were added. The resulting mixture was then ground at 30 rpm for 8 minutes using a ball mill. The resulting mixture was coated at room temperature at 30 mm / s onto a current collector called "EnSafe 65" from Armor to form a cathode, which was calendered at 95° C. to reduce the porosity. A thickness of 34 μm was obtained.
[0228] The preparation of the second cathode C2 in the form of a film in accordance with the present invention (i.e., using PVdF as an ion-nonconductive fluoropolymer) is as follows: 1.32 g of propylene carbonate (PC), 0.79 g of PMTFSI, 0.53 g of PVdF and 18 g of ACN are mixed in a beaker at 100 ° C and 300 rpm under magnetic stirring. Then, when a uniform result is obtained, 4.2 g of lithium manganese iron phosphate (LMFP) and 0.17 g of carbon black (KB) are added. The resulting mixture is then ground at 30 rpm for 8 minutes using a ball mill. The resulting mixture is coated at room temperature at 30 mm / s on a current collector called "EnSafe 65" from Armor to form a cathode, which is calendered at 95 ° C to reduce porosity. A thickness of 40 μm is obtained.
[0229] Table 5 below shows the mass percentages of various components present in the cathode prepared according to the above scheme:
[0230]
[0231] Table 5
[0232] Preparation of polymer electrolyte EP17 according to the present invention
[0233] The preparation of the EP17 polymer electrolyte in accordance with the present invention is as follows, which comprises PVdF as an ion-nonconductive fluoropolymer, PMTFSI as a cationic unipolar conductive polymer and propylene carbonate as a plasticizer: the components (ion-nonconductive fluoropolymer, cationic unipolar conductive polymer and plasticizer) are mixed with acetonitrile (ACN) in a beaker under magnetic stirring (300 rpm) at 100°C. For a mixture of 1 g of ion-nonconductive fluoropolymer and cationic unipolar conductive polymer, 1 g of plasticizer and 5 g of acetonitrile are used. After mixing, the resulting mixture is first coated at 8 mm / s at room temperature on the first side of a 16 μm thick porous polypropylene separator to form a thin film, which is then dried in a fume hood for a few minutes to evaporate the residual acetonitrile. The second side of the porous separator is then coated with the resulting mixture under the same conditions as the first coating.
[0234] Table 6 below shows the mass percentages of various components present in the polymer electrolyte EP17 prepared according to the above scheme, as well as its total thickness:
[0235]
[0236] Table 6
[0237] Performance of cathodes C1* and C2
[0238] For cathodes C1* and C2, both were assembled with EP17 polymer electrolytes with a 5 cm 2Catholyte-Cathode (CEC) Cells. Cells CEC1 and CEC2 with cathodes C1* and C2, respectively, were assembled by successive lamination in dry air at 75°C and 5 bar. The cells were placed in a compression system at 2 bar.
[0239] Impedance spectroscopy measurements were performed on each of the two cells. The ionic conductivity of the electrolyte was measured by impedance spectroscopy. The measurements were performed at 40°C in constant potential mode from 100 mHz to 1 MHz and an amplitude of 10 mV.
[0240] Figure 5 The inverse of the imaginary part Z'' in Ω is shown as a function of the real part Z' in Ω for the cathode C1* (dashed curve) and the cathode C2 (solid curve). Figure 5 The first semicircle obtained at high frequency (HF) is attributed to the contribution of polymer electrolyte + cathode electrolyte and the second semicircle is attributed to the cathode / current collector interface. For the CEC1 cell using the C1* cathode without PVDF, the impedance contributed by the polymer electrolyte + cathode electrolyte at HF is 490.9% higher. Since the polymer electrolyte EP17 is the same for CEC1 and CEC2 cells, it can be concluded that the use of PVDF in cathodes based on LMFP and PMTFSI and plasticized with PC helps to improve the ionic conductivity of the cathode electrolyte.
[0241] Table 7 below lists the characteristic frequency (in KHz) and impedance (in kΩ·cm) of the high frequency contribution of each cathode C1* and C2. 2 ).
[0242]
[0243] Table 7
[0244] Example 6: Preparation of a battery according to the present invention
[0245] Lithium electrolyte cathode cell (LEC1) was prepared by continuous lamination at 75 °C and 5 bar:
[0246] a polymer electrolyte EP3' according to the invention, identical to EP3 prepared in Example 1, except that the thickness was 18 μm instead of 34 μm,
[0247] -72µm thick lithium metal anode, and
[0248] - a cathode C3 according to the invention,
[0249] It was then placed in a compression system at 2 bar.
[0250] The theoretical mass capacity of battery LEC1 is 5 mAh / g.
[0251] The cathode C3 in the form of a film according to the present invention was prepared in advance as follows: 1.32 g of propylene carbonate (PC), 1.06 g of PMTFSI, 0.26 g of PVdF and 15 g of ACN were mixed in a beaker at 100 ° C and 300 rpm with magnetic stirring. Then, when a uniform result was obtained, 4.2 g of lithium manganese iron phosphate (LMFP) and 0.17 g of carbon black (KB) were added. The resulting mixture was then ground at 30 rpm using a ball mill for 8 minutes. The resulting mixture was coated at room temperature at 30 mm / s on a current collector called "EnSafe 65" from Armor to form a cathode, which was rolled at 95 ° C to reduce porosity. A thickness of 37 μm was obtained.
[0252] Table 8 below shows the mass percentages of the various components present in the cathode C3 prepared according to the above scheme:
[0253]
[0254] Table 8
[0255] Cycling was performed at 40 °C according to the following scheme (a 3 h pause was marked when the cell was placed in the oven):
[0256] -First, by applying relative Li / Li + Activation was performed for 10 hours at 3.3 V voltage;
[0257] -LEC1 is relative to Li / Li + Perform an initial C / 10 charge for a cutoff voltage of 4.2V;
[0258] - relative to Li / Li + The voltage was maintained at 4.2 V for 1 hour and 30 minutes, and then the voltage was changed to 4.2 V relative to Li / Li + D / 10 discharge is performed with a cut-off voltage of 2.5V;
[0259] -After the first cycle, the battery was cycled at C / 10-D / 5. The cut-off voltages for charge and discharge were still relative to Li / Li + is 4.2V and relative to Li / Li + is 2.5V. Each charge is relative to Li / Li + It was interrupted by a voltage of 4.2V and lasted for 1 hour and 30 minutes;
[0260] -After 40 cycles, the applied cycle becomes C / 4-D / 2.
[0261] After 358 cycles, the battery had a discharge capacity of 123 mAh / g and an efficiency equal to 99.8%.
[0262] Figure 6The capacity (in mAh / g) of the battery LEC1 is shown as a function of the number of cycles (solid diamond curve), and the efficiency (in %) of the battery LEC1 is shown as a function of the number of cycles (solid square curve).
[0263] Figure 7 The internal resistance Ri (in Ω·cm) of the battery LEC1 is shown when discharging (solid diamond curve) and loading (solid square curve). 2 ) as a function of the number of cycles.
[0264] Example 7: Preparation of a battery according to the present invention
[0265] Lithium electrolyte cathode cells (LEC2) were prepared by continuous lamination at 75 °C and 5 bar:
[0266] - the polymer electrolyte EP17 according to the invention was prepared as in Example 5,
[0267] -72µm thick lithium metal anode, and
[0268] - a cathode C3 according to the invention is prepared as in Example 6,
[0269] It was then placed in a compression system at 2 bar.
[0270] The theoretical mass capacity of battery LEC2 is 6 mAh / g.
[0271] Table 9 below shows the mass percentages of the various components present in the cathode C3 prepared according to the above scheme:
[0272]
[0273] Table 9
[0274] The same cycling protocol as described in Example 6 has been performed, except that the applied cycle became C / 4-D / 2 at the end of the 7th cycle, instead of the 40th cycle.
[0275] After 260 cycles, the battery had a discharge capacity of 123 mAh / g and an efficiency equal to 100%.
[0276] Figure 8 The capacity (in mAh / g) of the cell LEC2 is shown as a function of the number of cycles (solid diamond curve), and the efficiency (in %) of the cell LEC2 is shown as a function of the number of cycles (solid square curve).
[0277] Fig. 9 The internal resistance Ri (in Ω·cm) of the battery LEC2 is shown when discharging (solid diamond curve) and loading (solid square curve). 2) as a function of the number of cycles.
[0278] Example 8: Preparation of polymer electrolyte EP18 according to the present invention
[0279] As described in detail below, a polymer electrolyte comprising PVdF-HFP as an ion-nonconductive fluoropolymer, PMTFSI as a cationic unipolar conductive polymer, and propylene carbonate as a plasticizer was prepared.
[0280] The components (ion-nonconductive fluoropolymer, cationic unipolar conductive polymer and plasticizer) were mixed with acetonitrile (ACN) in a beaker under magnetic stirring (300 rpm) at 100° C. For 1 g of the mixture of ion-nonconductive fluoropolymer and cationic unipolar conductive polymer, 1 g of plasticizer and 5 g of acetonitrile were used. After mixing, the resulting mixture was coated onto a silicone-coated polyethylene terephthalate (PET) support at 8 mm / s at room temperature to form a thin film, which was then dried in a fume hood for a few minutes to evaporate the residual acetonitrile.
[0281] Table 10 below shows the mass percentages of various components present in the electrolyte prepared according to the above scheme and their thicknesses:
[0282]
[0283] Table 10
[0284] Polymer electrolyte EP18 was compared with polymer electrolyte EP1* prepared in Example 1 which was not in accordance with the invention (ie did not contain an ion-nonconductive fluorinated polymer).
[0285] Two lithium electrolyte lithium (LEL) batteries were then fabricated by sequentially laminating a lithium foil, a polymer electrolyte membrane, and another lithium foil at 75° C. under dry air.
[0286] For polymer electrolyte EP1* not in accordance with the invention, lamination was carried out at a pressure of 2 bar. For polymer electrolyte EP18 in accordance with the invention, lamination was carried out at a pressure of 5 bar.
[0287] The cells LEL1* and LEL18 containing polymer electrolytes EP1* and EP18 were placed in a compression system at 2 bar.
[0288] The ionic conductivity of polymer electrolytes EP1* and EP18 was measured as described in Example 1.
[0289] Fig.10 The S·cm of the polymer electrolytes EP1* (curves with solid circles connected by solid lines) and EP18 (curves with solid circles connected by dashed lines) are shown. -1The ionic conductivity is measured as a function of temperature (measured as 1000 / temperature, in Kelvin -1 In the presence of PVdF-HFP as an ion-nonconductive fluoropolymer, the ionic conductivity of the polymer electrolyte is improved.
Claims
1. A polymer composition, characterized in that It comprises at least one cationic unipolar conductive polymer, at least one plasticizer and at least one ion non-conductive fluorine-containing polymer, wherein the cationic unipolar conductive polymer is a homopolymer or copolymer comprising at least one organic polymer chain, an organic anion functional group forming a covalent bond with the organic polymer chain and a metal cation associated with the organic anion functional group.
2. The polymer composition according to claim 1, characterized in that The cationic monopolar conductive polymer is: - homopolymers which can be prepared from a) monomers comprising at least one organic anionic functional group covalently grafted onto said monomer and at least one metal cation associated with the organic anionic functional group; or - copolymers, which can be prepared from a) monomers comprising at least one organic anionic functional group covalently grafted onto said monomers and at least one metal cation associated with said organic anionic functional group, and b) at least one monomer different from monomer a), said monomer being selected from b1) monomers comprising at least one organic anionic functional group covalently grafted onto said monomers and at least one metal cation associated with said organic anionic functional group, and b2) organic monomers.
3. The polymer composition according to claim 1 or 2, characterized in that One or more than one of the metal cations associated with the organic anion functional group is selected from Li + Cations and Na + cation.
4. The polymer composition according to any one of the preceding claims, characterized in that One or more than one of the organic anion functional groups is a bissulfonylimide.
5. The polymer composition according to any one of the preceding claims, characterized in that The cationic monopolar conductive polymer is present in an amount of 5 to 40 wt % relative to the total weight of the polymer composition.
6. The polymer composition according to any one of the preceding claims, characterized in that The ion non-conductive fluorinated polymer is present in an amount of 5 to 45 wt % relative to the total weight of the polymer composition.
7. The polymer composition according to any one of the preceding claims, characterized in that The ion non-conductive fluoropolymer is selected from homopolymers and copolymers of vinyl fluoride (VF), homopolymers and copolymers of vinylidene fluoride (VdF), homopolymers and copolymers of tetrafluoroethylene (TFE), homopolymers and copolymers of chlorotrifluoroethylene (CTFE), homopolymers and copolymers of hexafluoropropylene (HFP), and mixtures thereof.
8. The polymer composition according to any one of the preceding claims, characterized in that The plasticizer is selected from the group consisting of linear carbonates and cyclic carbonates; fluorinated carbonates; nitriles; lactones; liquid linear polyethers and liquid cyclic polyethers; fluorinated polyethers; sulfur-containing solvents; phosphates; esters; and mixtures thereof.
9. The polymer composition according to any one of the preceding claims, characterized in that The plasticizer is present in an amount of 25 wt % to 90 wt % relative to the total weight of the polymer composition.
10. Use of a polymer composition according to any one of the preceding claims for the preparation of a polymer electrolyte and / or a positive electrode for a rechargeable battery.
11. A polymer electrolyte for a rechargeable battery, characterized in that: It comprises a polymer composition as defined in any one of claims 1 to 9, or a porous separator impregnated with a polymer composition as defined in any one of claims 1 to 9.
12. A positive electrode for a rechargeable battery comprising a positive electrode active material, a polymer composition, and optionally an electronic conductivity generator, characterized in that: The polymer composition is as defined in any one of claims 1 to 9.
13. A rechargeable lithium battery or a rechargeable sodium battery, characterized in that: It includes: - a negative electrode comprising lithium metal, sodium metal, a lithium metal alloy or a sodium metal alloy, - a positive electrode, which may be supported by a current collector, and - a polymer electrolyte, which is located between the positive and negative electrodes, Characterized in that the polymer electrolyte is as defined in claim 11, and / or the positive electrode is as defined in claim 12.
Citation Information
Patent Citations
Video signal recording and reproducing apparatus
EP0170267A2
Conductive polymer electrolyte for batteries
US20220029198A1